2014 International Joint Conference on Neural Networks (IJCNN) 2014
DOI: 10.1109/ijcnn.2014.6889625
|View full text |Cite
|
Sign up to set email alerts
|

Beating the S&P 500 index — A successful neural network approach

Abstract: The systematic trading of equities forms the basis of the asset management industry. Analysts are trying to outperform a passive investment in an index such as the S&P 500 Index. However, statistics have shown that most analysts fail to consistently beat the index. A number of Neural Network based methods for detecting trading opportunities on Futures contracts on the S&P 500 Index have been published in the literature. However, such methods have generally been unable to demonstrate sustained performance over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Some others [11] apply the LSTM combined with autoencoders to analyze stock price series in order to predict future prices. Besides predicting the price itself, there are also studies [12] [13] [14] building neural networks to predict the future direction of stock prices and aims to achieve high classification accuracy.…”
Section: Related Workmentioning
confidence: 99%
“…Some others [11] apply the LSTM combined with autoencoders to analyze stock price series in order to predict future prices. Besides predicting the price itself, there are also studies [12] [13] [14] building neural networks to predict the future direction of stock prices and aims to achieve high classification accuracy.…”
Section: Related Workmentioning
confidence: 99%
“…diction model is "consistent" with the trading strategy, e.g., the model predicts the direction of the price movement -but not the numerical value of the price -which is then used with a directional trading strategy. Sethi et al (2014) presented a neural network which used only two features to predict the direction (up or down) of next-day price movement for the largest 100 stocks (in terms of market capitalization) in the S&P 500 index. Those stocks were then combined into a portfolio in order to "beat" the index itself.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the open questions has been whether (and how) one can forecast the behavior of stocks and then act accordingly to generate "excess returns", i.e., profit in excess of those generated by the market itself (Fama and French, 1993). Towards that end, significant effort has been put into predicting the price of major U.S. stock indices such as the S&P 500 or the Dow Jones Industrial Average (DJIA) (Huck, 2009(Huck, , 2010Sethi et al, 2014;Krauss et al, 2017;Bao et al, 2017) as well as that of individual stocks, using techniques ranging from early linear models (Fama and French, 2004) to machine learning and neural network-based approaches (Sermpinis et al, 2013;Deng et al, 2017;Minh et al, 2018). There are two components which are generally part of the overall discussion on "intelligent" or automatic trading: a predictive model whose purpose is to anticipate an asset's future price, and a trading strategy which uses the model's predictions to generate profit.…”
Section: Introductionmentioning
confidence: 99%
“…For the past decade, deep neural networks have exhibited very good performance in many different fields such as computer vision, natural language processing and robotics. In recent years, it has been shown that deep learning is capable of identifying nonlinearities in time series data leading to profitable strategies [4][5][6].…”
Section: Introductionmentioning
confidence: 99%